Global lessons from Nigeria's ebolavirus control strategy. (2nd November 2015) - Elemuwa, Chris; Kutalek, Ruth; Ali, Mohammad; Mworozi, Edison; Kochhar, Sonali; Rath, Barbara; Safety Initiative, Vienna Vaccine
Abstract : The current Ebola virus disease outbreak challenged medical and public health systems in West Africa. In Nigeria, the existing infrastructure of the polio surveillance system was leveraged rapidly to contain the spread of Ebola virus. We highlight important lessons learnt from the successful implementation of Ebola virus disease surveillance strategies, which should be amplified further to prepare the ground for successful vaccination programs. Close collaboration between national and international stakeholders as well as public/private partnerships will be instrumental in future Ebola virus immunization strategies.